2024
DOI: 10.1021/acs.jafc.3c07536
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Natural Compounds from Herbs and Nutraceuticals in Alleviating Neurological Disorders: Targeting the Wnt Signaling Pathway

Lei Li,
Lin Wang,
Lijuan Zhang

Abstract: As an important signaling pathway in multicellular eukaryotes, the Wnt signaling pathway participates in a variety of physiological processes. Recent studies have confirmed that the Wnt signaling pathway plays an important role in neurological disorders such as stroke, Alzheimer's disease, and Parkinson's disease. The regulation of Wnt signaling by natural compounds in herbal medicines and nutraceuticals has emerged as a potential strategy for the development of new drugs for neurological disorders. Purpose: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 220 publications
(395 reference statements)
0
0
0
Order By: Relevance
“…In recent years, there has been a growing interest in neuropharmacology to discover new therapeutic agents that can improve the underlying mechanisms of NDs . One promising field is the utilization of natural products containing secondary metabolites found in plants, which play a crucial role in drug discovery since the synthetic drugs could damage neurons due to their toxicity and might contribute to brain disorders because they modulate the activity of multiple brain circuits controlling decision-making power, memory, learning, and other functions. , To date, several plant-derived compounds, including polyphenols and mostly flavonoids like myricetin, naringenin, curcumin, luteolin, fisetin, cornin, hesperidin, apigenin, and quercetin, have proved to be promising neuroprotective agents due to their antioxidant, free radical clearance, anti-inflammatory, and antimutative properties. ,, Studies have shown that flavonoids play a key role as antioxidants by activating SOD, CAT, and GPx, lowering GSH, and stopping lipid peroxidation. They also have anti-inflammatory properties that come from their ability to control tyrosine and serine–threonine kinases, cyclooxygenase (COX) and lipoxygenase suppression, and the production of proinflammatory molecules such as nitric oxide, prostaglandins, and leukotrienes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in neuropharmacology to discover new therapeutic agents that can improve the underlying mechanisms of NDs . One promising field is the utilization of natural products containing secondary metabolites found in plants, which play a crucial role in drug discovery since the synthetic drugs could damage neurons due to their toxicity and might contribute to brain disorders because they modulate the activity of multiple brain circuits controlling decision-making power, memory, learning, and other functions. , To date, several plant-derived compounds, including polyphenols and mostly flavonoids like myricetin, naringenin, curcumin, luteolin, fisetin, cornin, hesperidin, apigenin, and quercetin, have proved to be promising neuroprotective agents due to their antioxidant, free radical clearance, anti-inflammatory, and antimutative properties. ,, Studies have shown that flavonoids play a key role as antioxidants by activating SOD, CAT, and GPx, lowering GSH, and stopping lipid peroxidation. They also have anti-inflammatory properties that come from their ability to control tyrosine and serine–threonine kinases, cyclooxygenase (COX) and lipoxygenase suppression, and the production of proinflammatory molecules such as nitric oxide, prostaglandins, and leukotrienes.…”
Section: Introductionmentioning
confidence: 99%